SUATU KAJIAN TITIK TETAP PEMETAAN k-PSEUDONONSPREADING SEJATI DI RUANG HILBERT - Desi Rahmadani (Jurnal Matematika UNAND, 2013)
Let C be a subset of a real Hilbert space H. Let T : H ! H be a strictlyk-pseudononspreading mapping with a nonempty xed point set. Let ! 2 [k; 1) be xed.Let fTigNi=1be N k-strictly pseudononspreading mappings. In this paper, we study therelationship between of a xed point set of a k-strictly pseudononspreading mapping andother forms of certain combinations of some k-strictly pseudononspreading mappings inHilbert space.